Age at First Sexual Intercourse and Multiple Sexual Partnerships Among Women in Nigeria: A Cross-Sectional Analysis - Yaya, Sanni; Bishwajit, Ghose (Frontiers in Medicine, 2018)
Background Little is known about sexual behaviour such as first sexual intercourse and number of sexual partnerships among women in Nigeria. Early sexual debut is a widely recognized public health issue due to its influence on higher lifetime sexual partners which in turn is associated with increased vulnerability to pregnancy complications, HIV/AIDS and other and sexually-transmitted diseases. In the present study, we attempted to explore the patterns of age of sexual debut and multiple sexual partnerships among women of reproductive age in Nigeria. Methods Women who responded to the questions about the age at first sex and number of lifetime sex partners were selected from two latest rounds Nigeria Demographic and Health Survey (DHS). In total 60,611 women aged between 15-49 years were selected for this analysis. Age at sexual debut was used as the predictor of multiple sexual partnerships which was assessed by multinomial regression models with logit link function in complex sample analysis mode. Results The median age at first sex was 16 years (Interquartile range 16-24). Age at first sexual intercourse below the age of 19 years was reported by 30.8% of the women. Respectively 45.4% (95%CI=42.9 to 47.9) 49.8 % (95%CI=47.8 to 51.7) of the women reported experiencing first intercourse before reaching 15 and 17 years, whereas 46.9% (95%CI=45.2 to 48.7) of the women reported being monogamous and 47.2% (95%CI=45.6 to 48.8) and 47.6% (95%CI=43.8 to 51.3) had 2-3 and >3 lifetime sexual partners. In multivariable analysis after adjusting for confounding factors, women having sexual debut below 18 years were found to be significantly more likely to have 2-3 and more than 3 lifetime sexual partner. Conclusion The study concludes that an increasing proportion of Nigerian women are experiencing sexual debut before reaching 15 years. The findings suggest that early sexual debut is associated with multiple sexual partnerships which may increase the risk of STIs. Stakeholders in health care system need to be aware that early sexual debut can be associated with successive unsafe sexual practices which can lead to adverse health outcomes including HIV infection and STIs, early marriage, unwanted pregnancy and abortion.